(untitled) (Journal Intellectual Sufism Research (JISR), 2019)
Provision of donations in Indonesia has increasingly experienced significant development. The purpose of this study was to determine how the influence of religiosity, demographic, and motivation level variables of Surabaya State University Economics Faculty students on patterns of sharing behavior. Based on these results it can be concluded that the Faculty of Economics students do sharing behavior because it is influenced by demographic factors and motivation not because of the factor of religiosity, so that the higher or lower levels of student religiosity do not determine the amount of sharing made by students.